2014
DOI: 10.1590/0103-6440201300209
|View full text |Cite
|
Sign up to set email alerts
|

Root Canal Penetration of a Sodium Hypochlorite Mixture Using Sonic or Ultrasonic Activation

Abstract: The purpose of this ex vivo study was to determine, in "open" and "closed" systems, whether the design has an influence on the penetration length of sodium hypochlorite mixed with a radiopaque contrast medium, measured in millimeters, when delivered using positive pressure (PP) and using sonic (SI) or passive ultrasonic (PUI) activation. Sixty single-rooted teeth were divided into two groups: open and closed systems (n=30). Root canal shaping was performed to a working length of 17 mm. The samples were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
0
19
0
3
Order By: Relevance
“…For the final rinse, when assessing the volume of irrigant, 6 mL of NaOCl was used, based on a previous study which demonstrated the mechanical efficacy of this specific volume (Sedgley et al 2005). Similarly, the depth of needle placement and activation times were consistent with previous studies testing EA and PUI effect on penetration of irrigants using 'closed systems' (De Gregorio et al 2009, Merino et al 2013, Sainz-Pardo et al 2014), although a further study used a more coronally placed needle (WL-5), together with a shorter activation time (20 s) (Paragliola et al 2010). Arbitrary, however clinically relevant, total irrigation time and EDTA volume were used for the 'final rinse', due to the absence of published reference standards.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…For the final rinse, when assessing the volume of irrigant, 6 mL of NaOCl was used, based on a previous study which demonstrated the mechanical efficacy of this specific volume (Sedgley et al 2005). Similarly, the depth of needle placement and activation times were consistent with previous studies testing EA and PUI effect on penetration of irrigants using 'closed systems' (De Gregorio et al 2009, Merino et al 2013, Sainz-Pardo et al 2014), although a further study used a more coronally placed needle (WL-5), together with a shorter activation time (20 s) (Paragliola et al 2010). Arbitrary, however clinically relevant, total irrigation time and EDTA volume were used for the 'final rinse', due to the absence of published reference standards.…”
Section: Discussionmentioning
confidence: 84%
“…, Sainz‐Pardo et al . ), although a further study used a more coronally placed needle (WL‐5), together with a shorter activation time (20 s) (Paragliola et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penetration of solutions is enhanced by passive ultrasonic agitation (PUI), as suggested by several ex vivo studies in root canal systems with restricted flow through the apical foramen . A final rinse of EDTA with PUI has been associated clinically with a higher per cent of negative cultures, when compared with saline .…”
Section: Introductionmentioning
confidence: 99%
“…and Sáinz-Pardo et al 24 have positioned ultrasound as the most efficient method, but other authors state that sonic agitation obtains similar or even better results.…”
mentioning
confidence: 99%